Hole delocalization as a driving force for charge pair dissociation in organic photovoltaics. Issue 5 (27th February 2019) - Matheson, Andrew B.; Ruseckas, Arvydas; Pearson, Scott J.; Samuel, Ifor D. W.
Abstract : Hole polaron delocalization on polymer chains helps charge separation by lowering the free energy of the spatially separated charge pair. Abstract : Charge carrier photogeneration is studied in photovoltaic blends of the conjugated polymer PTB7 with the electron acceptor PC71 BM at low excitation densities using broadband transient absorption spectroscopy. In the optimized blend we observe a rise of hole polaron absorption on a 500 ps time scale which implies an increase of hole delocalization when photo-generated charge pairs dissociate into free charges. This concept is supported by the observed saturation of polaron absorption with electrochemical oxidation of polymer films, and the significant differences in transient absorption spectra observed in an inefficient blend due to bound charge transfer (CT) states. Our results suggest that hole polaron delocalization on polymer chains and entropy provide driving force for charge separation by lowering the free energy of the spatially separated charge pair. A potential barrier to the reformation of CT states appears as a result of carrier delocalization which also helps to reduce non-geminate carrier recombination.